Perancangan Sistem Informasi Pendataan dan Pelayanan Pendaftaran Pasien pada Klinik Pratama Lina Berbasis Website - Juraida, Juraida; Hariyanto, Eko (Jurnal Nasional Teknologi Komputer, 2023)
This research aims to design a web-based information system for patient data management and registration services at Klinik Pratama Lina. The study involves the analysis, design, and implementation phases to meet the needs of patient data management and registration in the clinic. The designed system includes interfaces for doctor registration, doctor data management, patient data management, treatment data management, and treatment report generation. The Waterfall method is utilized as the software development approach in this research. The study utilizes a sample dataset of 10 patients. The results demonstrate that the web-based information system for patient data management and registration services can enhance the efficiency and effectiveness of the patient registration process and data management at Klinik Pratama Lina. However, the research also identifies some limitations that need to be addressed, such as the possibility of input errors by users. This research contributes to the development of health information systems that can improve the quality of service and patient data management in the clinic.